The rise of an exciton in solid ammonia. Issue 6 (20th December 2021) - Cassidy, Andrew; James, Rachel L.; Dawes, Anita; Field, David
Abstract : An exciton gives rise to an absorption peak in vacuum ultra-violet spectroscopy of solid ammonia, with time-resolved evolution of the peak revealing the rate of nucleation and phase change. Abstract : We trace a polymorphic phase change in solid ammonia films through the emergence of a Frenkel exciton at 194.4 nm, for deposition temperatures of 48 K, 50 K and 52 K. Observations on a timescale of hours give unparalleled access to the individual processes of nucleation and the phase change itself. The excitonic transition is forbidden in the low temperature phase, but greater flexing of the solid state structure in the higher temperature phase makes the transition allowed, as the nano-crystals approach ∼30 unit cells through nucleation. We find activation energies of 21.7 ± 0.6 kJ mol −1 for nucleation and 22.8 ± 0.6 kJ mol −1 for the phase change, corresponding to the breaking of two to three hydrogen bonds.